Self-image of colostomy patients (Research, Society and Development, 2021)
This study aims to assess the self-image of ostomized patients. This is a bibliographic research, in which articles based on the present of the last five years were obtained. Nurses' work is fundamental for the management of care for ostomized patients. And the nurse must be prepared to provide all the information clearly, fulfilling certain steps, such as: hospitalization, preoperative exams, the trans operative, the post operative, ending with his discharge from hospital. In the care of patients with intestinal ostomies, it is concluded in the postoperative period, the occurrence of difficulties in accepting the new condition of ostomates, and the lack of knowledge about self-care. Then, there is a need for nursing consultation in the preoperative ostomy, in the sense of: enabling the patient to better accept the ostomy and its treatment; to be guiding the ostomate and his family regarding care, associations and support groups.